Гендерні проблеми у сучасному світі - Аріповська, В. В. (ХНУРЕ, 2020)
The article looks at the problems of gender equality in everyday life, development of gender issues and gender mainstreaming. The emphasis is on the relevance of such problems for young people. It’s possible to be sure that people can be a member, a woman is interpersonally human, I’m born with statistical characteristics, and I can’t stereotypically reckon a couple of people. The principle of gender equality manifests itself as a distinctive social construct, which allows for straightening for the simplification of suspension in the area of cognitive Rosum.
Keywords: філософія; гендерні проблеми